Strategy for the Development of a Sustainable Tourism Area Based on Disaster Mitigation in the Trusmi Batik Region - Rika Nurvilaelli Fahriyah; Mohd Abi Rafdi (Apollo: Journal of Tourism and Business, 2026)
Amid the risk of natural disasters, sustainable tourism development requires mitigation efforts capable of ensuring the safety of the area while supporting the community’s economic activities. The Trusmi Batik Area in Cirebon Regency, as a cultural tourism destination, faces the threat of flooding that has the potential to disrupt tourism activities, the batik trade, and community life. This study aims to develop a flood disaster mitigation strategy that can be implemented in the Trusmi Batik Area to reduce disaster risks and support the sustainability of tourism and trade activities in the region. The method used in this study is a descriptive qualitative approach through field observations and in-depth interviews with community leaders, batik business owners, and relevant agencies. The analysis indicates that flooding in the Trusmi Batik Area is influenced by physical factors such as high rainfall, a relatively concave topography, the proximity of residential areas to rivers, and inadequate drainage capacity, as well as non-physical factors such as land-use changes, low public awareness regarding environmental cleanliness, and suboptimal drainage management. Based on these findings, a disaster-mitigation-based tourism development strategy was formulated. It includes periodic drainage normalization and maintenance; environmental education and community cooperation; the provision of trash bins; the addition of green open spaces and infiltration wells; riverbank management; land-use control; and the strengthening of the Disaster-Resilient Village Program (Destana) through training and disaster simulations. This strategy is expected to reduce flood risks while supporting the development of the Trusmi Batik Area as a safer, more resilient, and sustainable tourism destination.